(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ameen MKM. 2024. Diversity of airborne fungi in cultured and urban sites in Basra Province, Iraq. Biodiversitas 25: 2870-2877. Atmospheric aerosols consist of particles with diverse sizes, shapes, fungal particles are relatively prevalent. They are related to air pollution and several plant, animal, and human health effects. This study was conducted to compare the airborne fungal biodiversity between cultivated and urban areas in Basra Province, Southern Iraq. Results showed that a total of 1654 fungal colonies consisted of 26 genera and two sterile mycelium belonging to 32 species. These fungal isolates belonged to three groups, namely Ascomycota, Zygomycota and Basidiomycota. Among them, Ascomycota had the highest percentage frequency (90.6%), followed by Zygomycota (6.25%) and Basidiomycota (3.12%). The highest i.e., 0.91and 0.9 fungal diversity was found in Abu Al-Khaseeb 2 and Ad-Dayr, respectively, while the lowest was in urban areas and desert nature as Um Qasr, Al-Zubair 0.78 for each. The highest frequency 18.2 10.9 8.8, and 8.5% of fungal isolates were Cladosporium herbarum, Aspergillus fumigatus, Aspergillus niger, and Penicillium sp., respectively. The highest similarity was 0.77 observed between the airborne fungal communities at the Alseeba and Altannumah sites. From the results of this study, it was concluded that airborne fungi can be influenced by the type of terrain they inhabit. There was greater diversity in cultivated areas compared to urban and non-cultivated areas.